Benefits of Measuring English as a Second Language Students’Learning - Kaseem, Ariel; Ahmad Khan , Yahya; Hasan, Mahmud (oneamd.com, 2025)
To reach effective learning goals, language instruction requires precise evaluation. The evaluation of suitable use of the English language is essential for both teaching and education. This document examines the connection between evaluation and instruction. In India, classrooms frequently symbolize diversity. Learners originate from various linguistic and cultural environments, and these aspects can serve as valuable assets instead of obstacles. Pupils acquire English as an additional language while educators evaluate their language proficiency. The framework of language evaluation is directly connected to the significance of education and learning. The language abilities of students and their impact on educational experiences can be assessed